2020
DOI: 10.1002/14651858.cd011365.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Tonsillectomy versus tonsillotomy for obstructive sleep-disordered breathing in children

Abstract: BackgroundObstructive sleep-disordered breathing (oSDB) is a condition encompassing breathing problems when asleep due to upper airway obstruction. In children, hypertrophy of the tonsils and/or adenoids is thought to be the commonest cause. As such, (adeno)tonsillectomy has long been the treatment of choice. A rise in partial removal of the tonsils over the last decade is due to the hypothesis that tonsillotomy is associated with lower postoperative morbidity and fewer complications. ObjectivesTo assess wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 88 publications
(4 reference statements)
0
37
0
Order By: Relevance
“…Partial tonsillectomy, also called tonsillotomy, is becoming more frequent in Sweden and has shown good treatment results 129,132 . Children seem to return faster to normal activity after tonsillotomy compared to tonsillectomy; nevertheless, the long-term effect and need for repeated surgery is still uncertain 133 . Children with non-severe OSA who receive intranasal steroids and leukotriene antagonists have shown improvement in their PSG parameters as well as their QoL [134][135][136] .…”
Section: Other Treatment Methodsmentioning
confidence: 99%
“…Partial tonsillectomy, also called tonsillotomy, is becoming more frequent in Sweden and has shown good treatment results 129,132 . Children seem to return faster to normal activity after tonsillotomy compared to tonsillectomy; nevertheless, the long-term effect and need for repeated surgery is still uncertain 133 . Children with non-severe OSA who receive intranasal steroids and leukotriene antagonists have shown improvement in their PSG parameters as well as their QoL [134][135][136] .…”
Section: Other Treatment Methodsmentioning
confidence: 99%
“…10 In these cases, tonsillectomy is usually associated with a higher risk of postoperative bleeding. 11 In the current study, 109 patients (58.6%) had one of the aforementioned indications. This further confirms the higher bleeding risk following surgery on inflamed tonsils.…”
Section: Discussionmentioning
confidence: 65%
“…Intracapsular tonsillectomy or tonsillotomy with partial resection of tonsils instead of the classical complete tonsillectomy is becoming more commonly used for the treatment of children with SDB. 55 Some studies showed that tonsillotomy resulted in a faster recovery and slightly lower risk of postoperative complications of bleeding and pain. However, more robust data from high-quality and long-term studies are needed to confirm its effectiveness and the risk of recurrence.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…However, more robust data from high-quality and long-term studies are needed to confirm its effectiveness and the risk of recurrence. 55 Children with risk factors for postoperative complications include young age less than 3 years, severe OSAS with an AHI score of >20 events per hour, cardiac complications, obesity, pre-existing structural comorbidities, or concurrent respiratory infections and should be subjected to at least a period of overnight in-patient observation postoperatively. 1 , 10 Adiposity and elevated leptin in obesity may also affect the metabolism of analgesic drugs such as morphine during postoperative care.…”
Section: Treatment Optionsmentioning
confidence: 99%